Pentahelix Collaboration In Community Protection-Based Latent Conflict Management In Mataram City In 2026 - Syaefullah; Wiredarme; Dwi Putri Yuliani (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This study aims to analyze the Pentahelix collaboration model in handling latent conflicts based on community protection in Mataram City. Latent conflict is a conflict that develops hidden in society and has the potential to become open conflict if not addressed early. Mataram City, as an area with a high level of social heterogeneity, has the potential for conflict influenced by social identity factors, population density, economic dynamics, and the spread of information on social media. The research method uses a qualitative approach with Spradley ethnographic data analysis through domain analysis, taxonomy, componential, and cultural themes. Data were obtained through in-depth interviews, observation, and documentation. The results of the study indicate that the handling of social conflicts has been sectoral and reactive, and has not optimally involved various stakeholders. The Pentahelix collaboration model involving the government, academics, the business sector, the community, and the media has proven to have the potential to increase the effectiveness of latent conflict management through an early detection system, multi-stakeholder coordination, and community participation. Integration with the community protection system strengthens the role of the community as the main actor in maintaining social stability. The results of the study resulted in an innovation in the form of a Pentahelix-based social conflict Early Warning System model that is able to detect potential conflicts early on in a collaborative manner. This model is expected to be a preventive strategy in maintaining public peace and order in a sustainable manner.